Kajian Terhadap Kedudukan Pemerintah Daerah Sebagai Pemohon Dalam Perlindungan Indikasi Geografis - Darwance, Darwance; sari, Rafiqa; Ramadhani, Tiara (PROGRESIF: Jurnal Hukum, 2022)
Data shows that Indonesia is a country that is rich in natural resources, even being the country with the most abundant natural resources in the world. From an intellectual property perspective, these potentials are products that can be protected based on communal ownership of geographical indications. After ratifying several international agreements, especially the TRIPs Agreement, Indonesia is obliged to have regulations that provide protection to geographical indications. In several existing regulations, local governments are given the authority as applicants when registering a product as a geographical indication at the ministry. In fact, the role of local governments is less than optimal, especially when viewed from the potential they have, plus regulations are not imperative. This research is normative with a statutory approach. From the results of the studies that have been carried out, it was found that the position of local governments in Law Number 20 of 2016 concerning Marks and Geographical Indications does not imperatively regulate the position of local governments specifically, so that only a few are registered due to the lack of local government contributions.